Two-step fermentation of cooked rice with Aspergillus oryzae and Clostridium acetobutylicum YM1 for biobutanol production - Ozturk, Abdullah Bilal; Al-Shorgani, Najeeb Kaid Nasser; Cheng, Shou; Arasoglu, Tulin; Gulen, Jale; Habaki, Hiroaki; Egashira, Ryuichi; Kalil, Mohd Sahaid; Yusoff, Wan Mohtar Wan; Cross, Jeffrey Scott (TAYLOR & FRANCIS LTD, 2022)
In Asia, uneaten cooked rice is the highest portion amongst many forms of food wastes that are thrown away. In order to make use of the thrown-away rice and potentially use it for liquid fuels, steamed Japanese rice was evaluated on biobutanol production through a two-step fermentation by amylase-producingAspergillus oryzae, and solvent-producingClostridium acetobutylicumYM1. The effects of sterilization and providing anaerobic conditions on solvent production in acetone-butanol-ethanol (ABE) fermentation cannot be underestimated. Several conditions, including aerobic, anaerobic, sterile, and non-sterile were investigated concerning the solvent production capability ofClostridium acetobutylicumYM1. The maximum solvent production was 11.02 +/- 0.22 g/l butanol and 18.03 +/- 0.34 g/l total ABE from 75 g/l dried rice. The results confirmed that the solvent production performance of the YM1 strain was not affected by the sterilization conditions. In particular, 10.91 +/- 0.16 g/l butanol and 16.68 +/- 0.22 g/l ABE were produced under non-sterile and aerobic conditions, which can reduce industrial-scale production costs.
Keywords: Solid-state fermentation; rice; solvent production; ABE fermentation; biobutanol; BUTANOL PRODUCTION; ACETONE; STRAW; ACID; HYDROLYSATE; IMPROVEMENT; STARCH; WASTE; Energy & Fuels